PELAKSANAAN PERSIAPAN PROGRAM GRAND STRATEGI KECAMATAN MANDAU DAN PINGGIR SEBAGAI KOTA TRANSIT DAN PETROPOLITAN - Risky Arya Putri; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Programs grand strategy is the development of four regional programs, one of which is a regional development program for the District of transit and petropolitan Saber and baseboards. Of the set target program's grand strategy has a span of five years, ie between years 2010-1015 but is expected this program will not selsesai up in any given year can be said that this program is still in the preparation stage is the preparation of the planning and preparation of the complete document infrastructure facilities to support the realization of Saber and Uptown District of the City of Transit and Petropolitan. In theory model of implementation by Van Meter and Van Horn there are six variables into factors that affect the implementation, namely: basic measures and policy objectives, policy resources, communication between the organization and activities of the implementing body characteristics implementers, economic conditions, social and political as well as the tendency executor. The method used in this study is a qualitative research technique is purposive sampling conducted on key informants and analyzed using the data tringulasi. In this study, the informant is the Head of programming and monitoring of the Regional Development Planning Agency Bengkalis, Secretary of the Department of Public Works Bengkalis, Secretary of the Department of City Planning, Spatial and Settlements Bengkalis, Secretary and Secretary of the District Head Saber Edge sub-district. Based on research conducted by perpedoman on the concept of the Grand Strategy Implementation Programme Preparation Saber and Uptown District of the City of Transit and Petropolitan. Until now entering the final period of predetermined targets, the preparation of the program is assessed not maximized and only reached the stage of preparation of the documents alone while planning for infrastructure facilities and infrastructure that supports only up to the workmanship roundabout when seen today has not shown progress significant making preparations other facilities not yet done. Keywords: Grand Strategy, transit and petropolitan, implementation, preparation.